Pengaruh Angka Buta Huruf Terhadap Tingkat Kemiskinan di Provinsi Nusa Tenggara Barat - Oktaviani, Reni; Moya, Hendrikus; Indriani, Ria; Aloiya, Sindy (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2024)
One factor that might affect poverty levels is education. For a country, combating poverty is not an easy or straightforward task. In this study, the illiteracy rate is used as a measure of education. Also, West Nusa Tenggara Province has seen a general decline in the illiteracy rate within the last five years. The purpose of this study is to analyze the relationship between poverty and illiteracy in West Nusa Tenggara province in the year 2022. The illiteracy rate and percentage of the impoverished population are the variables used in this study, which draws data from the Central Statistics Agency of West Nusa Tenggara Province. According to the study's findings, illiteracy affects the poverty rate by 26%, while other variables account for the remaining 74%. A 0.469-unit increase in the poverty rate occurs for every 1-unit rise in the illiteracy rate.